Early and long-lasting protection from arthritis in tumour necrosis factor α (TNFα) transgenic mice vaccinated against TNFα. Issue 9 (27th November 2007) - Delavallée, L; Le Buanec, H; Bessis, N; Assier, E; Denys, A; Bizzini, B; Zagury, D; Boissier, M-C
Abstract : Objective: To evaluate the effect in mice with arthritis of active anti-tumour necrosis factor (TNF)α immunotherapy based on a keyhole limpet haemocyanin–human TNFα heterocomplex (hTNFα kinoid or TNFK) adjuvanted in incomplete Freund adjuvant. Immunotherapy was evaluated also with methotrexate. Methods: Human TNFα-transgenic mice received TNFK with or without methotrexate. Follow-up ranged from 6 weeks (short term) to 17 weeks (long term). Arthritis was evaluated clinically and histologically. Monitoring included titration of anti-hTNFα antibodies by ELISA and neutralisation assay. Results: Vaccination with TNFK was associated with rapid-onset, long-lasting protection. Long-term results showed significantly milder arthritis in vaccinated animals than in control animals at the peak of the disease. Vaccination was followed by resolution of the clinical evidence of arthritis, contrasting with severe progressive arthritis in the control group. Histological improvements with decreased inflammation and destruction were noted in all immunised groups, even after the shortest follow-up (6 weeks). High titres of neutralising anti-hTNFα antibodies were detected as early as the fifth week post immunisation and persisted over time. Methotrexate given concomitantly with the vaccine did not influence either the effect on arthritis or the anti-hTNFα antibody titres. Conclusion: Anti-cytokine induction of autoimmune protection against chronic hTNFα overproduction is an efficient alternative to TNFα blockade in experimental arthritis and can be achieved using a TNFK vaccine.